Intellectual capital and bank profitability: New evidence from Vietnam - Tu DQ Le; Dat T. Nguyen (Cogent Business & Management, 2020)
This study empirically examines the impact of intellectual capital on bank risk-adjusted returns in Vietnam between 2007 and 2019 using the system generalized method of moments (GMM). The findings show the positive impacts of value-added intellectual coefficient (VAIC) and its components (human capital efficiency (HCE), capital employed efficiency (CEE), and structural capital efficiency (SCE)) on bank profitability. However, the results show an inverted U-shaped relationship may exist in the case of VAIC, HCE, and CEE. Also, the positive impacts of VAIC and HCE on bank profitability are true to the case of state-owned commercial banks while for foreign-owned banks the positive effect is more with HCE. Therefore, this study provides significant implications for policy-makers, management, and academics.
Keywords: G21; G28; G30; 650; intellectual capital; risk-adjusted returns; Vietnam; system GMM